التنظيم القانوني للقرارات الإدارية في النظام السعودي - بدران، دعاء محمد إبراهيم إبراهيم (جامعة زيان عاشور الجلفة, 2022)
يعد القرار الإداري أهم التصرفات القانونية التي تصدر عن الإدارة العامة، وتمثل سلطة الإدارة في إصدار القرارات الإدارية المظهر الرئيسي والأساسي لوسائل الإدارة في مباشرة كافة أوجه نشاطها، فهو أهم وأخطر امتيازات السلطة الإدارية التي لا غني عنها، فالإدارة لا تستطيع في غالب الأحيان أن تمارس عملها إلا من خلال هذه القرارات. ولما كان النظام السعودي يتمتع بخصوصية في التنظيم، نظراً لاعتماد النظام ككل على الشريعة الإسلامية كمصدر رئيسي للتشريع، مع مراعاة التطور الكبير في أساليب إصدار القرارات الإدارية، فإن هذا البحث يلقي الضوء على التنظيم القانوني للقرارات الإدارية في النظام السعودي وصولا إلى أخذ تصور كامل للتوصيف القانوني للقرارات الإدارية في النظام السعودي. The administrative decision is the most important legal action issued by the public administration, and the authority of the administration in issuing administrative decisions is a major aspect of the management’s means in its activity. The administrative decision is the most important and indispensable privilege of the administrative authority. Saudi law has a peculiarity in organization, because it relies on Islamic law as a main source of legislation, taking into account the great development in the methods of issuing administrative decisions, and this research sheds light on the legal organization of administrative decisions in Saudi law so that we can take a full picture of the legal description of administrative decisions in Saudi law.
Keywords: القرارات الإدارية -- التنظيم القانوني -- التشريعات السعودية